Electrophysiological Abnormalities in VLCAD Deficient hiPSC-Cardiomyocytes Do not Improve with Carnitine Supplementation - Verkerk, Arie O.; Knottnerus, Suzan J. G.; Portero, Vincent; Bleeker, Jeannette C.; Ferdinandusse, Sacha; Guan, Kaomei; IJlst, Lodewijk; Visser, Gepke; Wanders, Ronald J. A.; Wijburg, Frits A.; Bezzina, Connie R.; Mengarelli, Isabella; et al. (Frontiers in Pharmacology, 2021)
Patients with a deficiency in very long-chain acyl-CoA dehydrogenase (VLCAD), an enzyme that is involved in the mitochondrial beta-oxidation of long-chain fatty acids, are at risk for developing cardiac arrhythmias. In human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs), VLCAD deficiency (VLCADD) results in a series of abnormalities, including: 1) accumulation of long-chain acylcarnitines, 2) action potential shortening, 3) higher systolic and diastolic intracellular Ca2+ concentrations, and 4) development of delayed afterdepolarizations. In the fatty acid oxidation process, carnitine is required for bidirectional transport of acyl groups across the mitochondrial membrane. Supplementation has been suggested as potential therapeutic approach in VLCADD, but its benefits are debated. Here, we studied the effects of carnitine supplementation on the long-chain acylcarnitine levels and performed electrophysiological analyses in VLCADD patient-derived hiPSC-CMs with a ACADVL gene mutation (p.Val283Ala/p.Glu381del). Under standard culture conditions, VLCADD hiPSC-CMs showed high concentrations of long-chain acylcarnitines, short action potentials, and high delayed afterdepolarizations occurrence. Incubation of the hiPSC-CMs with 400 µM L-carnitine for 48 h led to increased long-chain acylcarnitine levels both in medium and cells. In addition, carnitine supplementation neither restored abnormal action potential parameters nor the increased occurrence of delayed afterdepolarizations in VLCADD hiPSC-CMs. We conclude that long-chain acylcarnitine accumulation and electrophysiological abnormalities in VLCADD hiPSC-CMs are not normalized by carnitine supplementation, indicating that this treatment is unlikely to be beneficial against cardiac arrhythmias in VLCADD patients.